A RARE CAUSE OF ENCEPHALOPATHY IN CHILDREN: PRES SYNDROME - Tosun, Demet; Akçay, Nihal; Oğur, Mustafa; Şevketoplu, Esra (MNJ (Malang Neurology Journal), 2024)
Background: Major clinical symptoms of posterior reversible encephalopathy syndrome include headache, mental status changes, visual disturbances, seizures, especially in the posterior cerebral region, and radiographic findings of vasogenic edema, especially in the posterior cerebellar region. Case Report: We present our 6-year-old patient with chronic renal failure. admitted to our pediatric emergency department with an acute hypertensive crisis. Generalized tonic-clonic seizures and mental status changes were accompanied in the follow-up of the patient whose GCS was 11; With symptomatic treatment, regression in both clinical complaints and imaging findings of our patient is consistent with Posterior reversible encephalopathy syndrome (PRES). Conclusion: It is imperative to consider PRES syndrome as a differential diagnosis when pediatric patients exhibit symptoms of acute encephalopathy. It is crucial to emphasize the critical nature of early diagnosis and treatment, as well as the potential for complete recovery without sequelae.